DEVELOPMENT AND VALIDATION OF A FAST AND SENSITIVE UHPLC-PDA METHOD FOR THE QUANTIFICATION OF URSOLIC ACID IN POLY(L-LACTIC ACID) NANOCAPSULES - CARLETTO, BRUNA; LYRA, AMANDA MARTINEZ; KOGA, ADRIANA YURIKO; NOVATSKI, ANDRESSA; MAINARDES, RUBIANA MARA; LIPINSKI, LEANDRO CAVALCANTE; FARAGO, PAULO VITOR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present study is to develop and validation of a ultra-high performance liquid chromatography (UHPLC) method to determine the ursolic acid content and its encapsulation efficiency (EE) in lipid-core nanocapsules prepared from poly (L-lactic acid). Methods: A simple UHPLC-PDA method was developed and validated for the quantitative determination of ursolic acid in poly(L-lactic acid) nanocapsules. The chromatographic conditions used were: RP-C18 column, isocratic mobile phase containing acetonitrile:water (92:8, v/v), flow rate of 0.8 ml/min, column temperature of 50°C, and detection at 203 nm. The following parameters were evaluated: Specificity, linearity, limits of detection and quantification, precision, accuracy, and robustness. Results: The method was specific to the ursolic acid and linear (r=0.9998) in the range of 10–100 μg/ml. The limits of detection and quantification were 1.35 and 4.10 μg/ml, respectively. The precision was demonstrated by a relative standard deviation less than 2%. Adequate accuracy (98.35%±0.82) was obtained. Changes in flow rate, mobile phase, and column temperature did not significantly alter the peak area and the retention time of the ursolic acid. The mean EE was 99.89%. Conclusion: The method proved to be fast, sensitive, and simple for quantifying ursolic acid in nanocapsules and was successfully used for determining the EE.